2013
DOI: 10.1038/oncsis.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal kinase Nek2 cooperates with oncogenic pathways to promote metastasis

Abstract: Centrosomal kinase Nek2 is overexpressed in different cancers, yet how it contributes toward tumorigenesis remains poorly understood. dNek2 overexpression in a Drosophila melanogaster model led to upregulation of Drosophila Wnt ortholog wingless (Wg), and alteration of cell migration markers—Rho1, Rac1 and E-cadherin (Ecad)—resulting in changes in cell shape and tissue morphogenesis. dNek2 overexpression cooperated with receptor tyrosine kinase and mitogen-activated protein kinase signaling to upregulate activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 50 publications
5
79
0
Order By: Relevance
“…Previous studies suggested that the overexpression of NEK2 promotes activation of AKT, a potent and critical oncogene for a variety of malignancies (26,27). Moreover, the PI3K/AKT signaling pathway plays an important role in upregulating MMP expression (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the overexpression of NEK2 promotes activation of AKT, a potent and critical oncogene for a variety of malignancies (26,27). Moreover, the PI3K/AKT signaling pathway plays an important role in upregulating MMP expression (28).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that NEK2 may be involved in tumor progression through the influence of other tumor pathways. The elevation of NEK2 contributes to the activation of the PI3K/AKT signaling pathway, a potent and critical oncogene for a variety of malignancies (26,27). Moreover, the PI3K/AKT signaling pathway plays an important role in upregulating MMP expression (28), and aberrant AKT signaling could promote cell proliferation in HCC cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…As a cell cycle-regulated serine/threonine kinase, Nek2A may undergo autophosphorylation, because the phosphoamino acid analysis of labeled Nek2 protein showed predominant phosphoserine and minor phosphothreonine. Studies in Drosophila melanogaster and human diseases of Nek2 illustrated that overexpression of Nek2 correlated to activation of the Akt and JNK pathways, as well as upregulation of Wnt signaling, which are highly conserved in multiple species and involved in cellular growth and survival [40,41]. Therefore, Nek2 has been emerged as an important oncogene due to its regulatory role in mitosis and cancer related signaling pathways [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that NEK2 silencing by shRNAs reduces tumor cell progression by interference with chromosomal segregation in human breast cancer cell lines in vitro and in fat pad xenograft mouse models, leading to aneuploidy and subsequent cell death (35). Another study indicated that in human lung and colorectal cancer cell lines, NEK2 plays a critical role in the subcellular transfer of β-catenin from the plasma membrane to the cytoplasm and the nucleus, leading to an invasive cellular phenotype in vitro and in vivo (11,36). Our data indicated that NEK2 expression was elevated in the stem cell fraction in GBM and was essential for GSC stemness in vitro and in vivo.…”
Section: Methodsmentioning
confidence: 99%